A simple fabrication of CH3NH3PbI3 perovskite for solar cells using low-purity PbI2. (January 2017) - Guo, Nanjie; Zhang, Taiyang; Li, Ge; Xu, Feng; Qian, Xufang; Zhao, Yixin
Abstract: The CH3 NH3 PbI3 (MAPbI3 ) perovskite was usually prepared by high-purity PbI2 with high cost. The low cost and low-purity PbI2 was seldom reported for fabrication of MAPbI3 because it cannot even dissolve well in widely adopted solvent of DMF. We developed an easy method to adapt low-purity PbI2 for fabrication of high quality MAPbI3 just by the simple addition of some hydrochloric acid into the mixture of low-purity PbI2, MAI and DMF. This straightforward method can not only help dissolve the low quality PbI2 by reacting with some impurities in DMF, but also lead to a successful fabrication of high-quality perovskite solar cells with up to 14.80% efficiency comparable to the high quality PbI2 precursors.